Gnieźnieńska „genealogia" biskupów ziem polsko-litewsko-ruskich. Wokół Prałatów i kanoników katedry metropolitalnej gnieźnieńskiej Jana Korytkowskiego - Prokop, Krzysztof R. (Ecclesia. Studia z Dziejów Wielkopolski, 2014)
In the Old Polish period many members of the chapter of the archcathedral in Gniezno became at various stages of their church career members of the episcopate. They are, among others, described on the pages of a fundamental compendium titled Prałaci i kanonicy katedry metropolitalnej gnieźnieńskiej (The Prelates and Canons of the Gniezno Metropolitan Cathedral) written by Jan Korytkowski (1824-1888), himself a clergyman (he died as a bishop-nominee). He pays much attention to such questions as where, when and through whose ministry a particular representative of the episcopate received his episcopal consecration. The author of the article analyzes the provided data and adds numerous supplementary  comments.